Open market value provision as an anti-abuse measure in Serbian VAT legislation - Kostić Jelena Ž.; Vasović Miloš R. (Strani pravni život, 2024)
In the value-added tax system of the European Union, the open market value provision is considered as a special anti-abuse measure. Serbian Law on Value-Added Tax allows the taxpayers to make supplies for the consideration lower than the open market value. In addition, the Law does not stipulate any anti-abuse measure similar to the open market value provision in EU VAT legislation. Between the connected parties, this could become an incentive to taypayers to abuse VAT in certain situations. Within the current domestic legislation, the principle of facticity is the only alternative measure to combat VAT abuse, but it should not be used for the correction of the taxable amount following the open market value. The stipulation of the open market value provision in domestic VAT legislation would be highly beneficial from the point of harmonizing the Serbian regulations with those of the European Union, as well as from the point of the protection of national fiscal system. Following the hypothesis that national legislation needs to be further harmonised with the EU VAT legislation, the authors in this paper used the normative dogmatic and content analysis methods with particular reference to the case law of the Court of Justice of the European Union.